The Form and Creative Process of Nyi Pandanaran as a Female Warrior Dance - Sangghita Anjali; Soemaryatmi; R. M. Pramutomo (Gondang: Jurnal Seni dan Budaya, 2025)
The dance work Nyi Pandanaran Prajurit Perempuan is a traditional solo performance inspired by the historical figure Nyi Pandanaran, who accompanied her husband in developing the Kadipaten Semarang during the 16th century. This study aims to explore the form and creative process behind the choreography, highlighting the representation of women's resilience, participation, and leadership. Using a practice-based research approach, the choreographer developed movements derived from traditional Javanese dance styles of Surakarta, Yogyakarta, and Semarang, integrated with properties such as fans, bows, and daggers to symbolize strength and femininity. The performance is divided into three main scenes: the opening reflects firmness and determination; the middle portrays grace, prayer, and spiritual strength; and the final scene conveys courage and martial prowess. The dance is supported by musical arrangements that combine Javanese gamelan with modern instruments like saxophone and trumpet, as well as realistic makeup and military-inspired costumes that emphasize character expression. Lighting design further enhances the performance by dividing stage space and symbolizing emotional tones through the use of red and gold hues. The work ultimately presents a nuanced narrative of a woman warrior’s struggle and leadership in safeguarding her land, illustrating themes of emancipation and national devotion. Through this creation, the choreographer underscores the potential of women to embody both strength and grace within cultural and historical contexts.